Knowledge Cities in the Process of Shaping Territorial Competitiveness and Cohesion - Parteka, Tomasz (Journal of Public Governance, 2010)
Below article concerns new interpretations of developing urban structures: from functional space to creative space. The article also concerns symptoms of metropolisation of Polish cities, with special role of knowledge in the urban development in innovative regions. The role of knowledge cities in the European documents on social, economical and territorial cohesion had been analysed as well. Polish cities are about to face great opportunity of using financial support instruments to strengthen their competitive position in the European space of knowledge.